Creative Hubs in Question Place, Space and Work in the Creative Economy - Gill, Rosalind; Pratt, Andy C.; Virani, Tarek E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Creative hubs have become a cornerstone of economic and cultural policy with only the barest amount of discussion or scrutiny. This volume offers the first interrogation of creative hubs, with ground-breaking critical writing from a combination of established scholars and new voices. Looking across multiple sites trans-nationally, and combining theoretical and empirical reflections, it asks: what are creative hubs, why do they matter, and are they making the world a better place? Creative Hubs in Question discusses creative hubs in relation to debates about creative cities, co-working spaces and workers' co-operatives. Featuring case studies from Argentina to the Netherlands, and Nigeria to the UK, the contributions address how hubs are situated in relation to projects of equality and social justice, and whether and in what ways they change the experiences of the creatives who work in them. Drawing on a range of disciplinary perspectives including sociology, geography, economics, media and communications, culture and creative industries, critical policy studies, gender studies, race and ethnicity, and urban studies, this collection will be of interest to policy makers, academics, scholars, students and practitioners across these fields. .
Chapter 1: Introduction; Andy C. Pratt, Tarek E. Virani and Rosalind Gill -- PART 1: LOOKING INSIDE THE CLUSTER -- Chapter 2: Herding Cats: Co-Work, Creativity and Precarity in Inner Sydney; George Morgan and James Woodriff -- Chapter 3: Curating Strangers; Janet Merkel -- Chapter 4: Creative Hubs, Cultural Work and Affective Economies: Exploring 'Unspeakable' Experiences for Young Cultural Workers; David Lee -- Chapter 5: Hubs vs Networks in the Creative Economy: Towards a 'Collaborative Individualism'; Carolina Bandinelli and Alessandro Gandini -- Chapter 6: Community-Led Co-Working Spaces: From Colocation to Collaboration and Collectivization; Vasilis Avdikos and Eirini Iliopoulou -- Chapter 7: Hip Hub? Class, Race and Gender in Creative Hubs; Tarek E. Virani and Rosalind Gill -- Chapter 8: Creative Hubs: A Cooperative Space?; Marisol Sandoval and Jo Littler -- PART 2: LOOKING OUTSIDE THE CLUSTER -- Chapter 9: Istanbul's Sounds and its 'Creative' Hubs: Creative Actors Articulating the City into Transnational Networks through Music; Ceren Mert -- Chapter 10: Nairobi's iHub: Technology for Society; Øyvind Økland -- Chapter 11: Producing Values: Impact Hub Birmingham as Co-Working and Social Innovation Space; Paul Long and Annette Naudin -- Chapter 12: Punk Rock Entrepreneurship: All-Ages DIY Music Venues and the Urban Economic Landscape; Michael Seman -- Chapter 13: Thinking through the Creative Hub in Peripheral Places: A Long-View of the Dartington Hall Experiment in Rural Reconstruction through Creativity; Nicola J. Thomas -- Chapter 14: From Making to Displaying: The Role of Organizational Space in Showing Creative Coolness at the Volkshotel; Boujke Cnossen -- Chapter 15: The City as a Creative Hub: The Case of the Fashion Industry in Milan, Italy; Marianna d'Ovidio and Valentina Pacetti -- Chapter 16: Grassroots Creative Hubs: Urban Regeneration, Recovered Industrial Factories and Cultural Production in Buenos Aires and Rio de Janeiro; Cecilia Dinardi -- Chapter 17: Creative Hubs and the Night Time Economy: Convergent or Divergent?; Andy C. Pratt and Tom Gill -- Chapter 18: Exploring the Relationship between Creative Hubs and Urban Policy in East London; Tarek E. Virani -- Chapter 19: Universities as Creative Hubs: Modes and Practices in the UK Context; Daniel Ashton and Roberta Comunian.
Keywords: Industrial sociology; Sociology, Urban; Economic sociology; Sociology of Work; Urban Sociology; Economic Sociology